Diagnostic Sensitivity of NLR and PLR in Early Diagnosis of Gastric Cancer. (7th March 2020) - Fang, Tianyi; Wang, Yimin; Yin, Xin; Zhai, Zhao; Zhang, Yu; Yang, Yongheng; You, Qi; Li, Zhiguo; Ma, Yan; Li, Chunfeng; Song, Haibin; Shi, Huawen; et al.
Abstract : The neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) are markers of systemic inflammation. However, there is little evidence of the value of inflammation in the early diagnosis of gastric cancer (GC). A total of 2, 606 patients diagnosed with GC in the past three years and 3, 219 healthy controls over the same period were included in this study. Peripheral blood samples were obtained to analyze the NLR, PLR, carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA19-9). The optimal cutoff levels for the NLR and PLR were defined by receiver operating characteristic (ROC) curve analysis (NLR = 2.258, PLR = 147.368 ). The value of different biomarkers for diagnosing GC was compared by the area under the curve (AUC). The NLR and PLR showed diagnostic sensitivity in GC (AUC = 0.715, AUC = 0.707 ). Using the Bonferroni correction, the NLR and PLR were superior to CEA and CA19-9 in the diagnosis of GC (P < 0.0001 ). The systemic inflammatory markers were significantly higher in the early stage of GC than tumor markers. After grouping patients and healthy controls by gender, we found that the diagnostic significance of combined NLR and PLR for GC was greater in male patients than in female patients (P < 0.0001 ). The diagnostic value of the NLR and PLR in GC is higher than that of the traditional tumor markers CEA and CA19-9. Systemic markers of inflammation are more valuable in male than female patients.